The relationship between vaginal and endometrial microbiota and the outcome of Frozen-Thawed embryo transfer during hormone replacement cycles - Lili Chen; Yi Ke; Huanhuan Guo; Bingping Wu; Lan Liu (BMC Microbiology, 2025)
Abstract Objective To investigate whether vaginal and endometrial microbiota impact pregnancy outcomes in frozen embryo transfers (FET) during hormone replacement cycles. Methods This retrospective cohort study analyzed 51 first-time FET patients from January 2021 to December 2022. Using 16 S rRNA sequencing, patients were stratified based on uterine microbiota composition into Lactobacillus-dominant (LD, 20 cases) and non-Lactobacillus-dominant (NLD, 31 cases) groups based on uterine microbiota. Vaginal (A1, A2) and uterine (B1, B2) microbiota were compared, along with pregnancy outcomes. Results Sequencing yielded 5,753,727 valid sequences and 1,545 OTUs. Alpha diversity showed lower Shannon index (P=0.034) and higher Simpson index in B1 vs. B2 (P=0.017), indicating reduced diversity in B1. Beta diversity analysis revealed more concentrated and similar microbial composition in B1, with significant differences between B1 and B2 (Anosim R = 0.3812, P = 0.001). B1 had higher abundance of Firmicutes and Lactobacillus, while B2 had more Proteobacteria and potential pathogens. Clinical pregnancy rate (75.00%) and live birth rate (65.00%) were higher in LD compared to NLD (45.16% and 29.03%, respectively, P = 0.036 and P = 0.011). Conclusion Vaginal microbiota do not fully reflect uterine microbiota. Dominance of Lactobacillus in the uterine microbiome is beneficial for favorable FET outcomes, while the presence of non-Lactobacillus dominant species may negatively impact FET results.